2017
DOI: 10.1371/journal.pone.0182955
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Fe2O3 crystal phases on CO2 hydrogenation

Abstract: The effect of Fe2O3 crystal phases on their performance in CO2 hydrogenation was studied. α-Fe2O3 crystal was prepared by precipitation method from Fe(NO3)3·9H2O and (NH4)2CO3, and γ-Fe2O3 was prepared by grinding Fe(NO3)3·9H2O and L(+)-Tartaric acid in agate mortar completely. The crystal phases of Fe2O3 influence the distribution of promoter Zn, K and Cu on catalysts. The dispersity of K on γ-Fe2O3 surface is higher than α-Fe2O3. On the contrary, Cu and Zn are more dispersive on α-Fe2O3 surface than γ-Fe2O3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…The diffraction pattern of GO was matched with previously reported one [23]. [24]. Moreover, Cu-Fe/GO has also shown diffraction peaks similar to Fe/GO.…”
Section: Xrd and Ft-ir Analysissupporting
confidence: 88%
“…The diffraction pattern of GO was matched with previously reported one [23]. [24]. Moreover, Cu-Fe/GO has also shown diffraction peaks similar to Fe/GO.…”
Section: Xrd and Ft-ir Analysissupporting
confidence: 88%
“…Greenhouse gases, especially CO 2 , constantly promote the greenhouse effect and hence contribute immensely to the environmental misbalance. Therefore, to achieve environmental sustainability, researchers are trying to capture CO 2 , using highly stable and porous structures, , and convert it into useful products such as CO, and lower and higher molecular weight hydrocarbons ,,− via photocatalytic, , electrocatalytic , and photoelectrocatalytic , conversion. Correspondingly, due to adequate interfacial interaction of CO 2 , H-NPs and M-NPs are found useful and widely reported for CO 2 conversion.…”
Section: Environmental Remediation By Hematite and Magnetitementioning
confidence: 99%
“…Ning et al synthesized hematite (α-Fe 2 O 3 ) by precipitation method using (NH 4 ) 2 CO 3 , Fe­(NO 3 ) 3 ·9H 2 O, while γ-Fe 2 O 3 by grinding l -(+)-tartaric acid and Fe­(NO 3 ) 3 ·9H 2 O. It was reported that the dispersity of cocatalyst K on α-Fe 2 O 3 was significantly lower than the γ-Fe 2 O 3 surface, while Cu and Zn acted contrary, thus making it more reactive in CO 2 hydrogenation . Similarly, the nanocomposite of α-Fe 2 O 3 with γ-C 3 N 4 , which was synthesized by a wet-chemical process, is found exceptionally active toward photocatalytic phenol degradation and CO 2 conversion to CO and CH 4 products, compared to bare α-Fe 2 O 3 .…”
Section: Environmental Remediation By Hematite and Magnetitementioning
confidence: 99%
See 1 more Smart Citation
“…For iron-based oxides, generally, the γ-Fe 2 O 3 crystalline phase shows better activity than α-Fe 2 O 3 in NH 3 -SCR [7,17,18] and other catalytic reactions, such as CO 2 hydrogenation, photodecomposition of H 2 S, and NO reduction by CO [19][20][21]. However, the γ-Fe 2 O 3 active phase is thermally unstable and undergoes irreversible transformation to α-Fe 2 O 3 at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%